Juristic differences over the implementation of qiṣāṣ against a Muslim who kills a non-Muslim - Amanullah, Muhammad (Brill, 2018)
Muslim jurists differ on whether Muslims who murder non-Muslims should be sentenced to death or not. Although Ḥanafī jurists maintain that they should be, most Muslim jurists hold that they should not. Modern scholars such as ʿAwdah, El-Awa and others have discussed the issue. Based on classical and modern fiqh (Islamic law) literature, this article examines the principal arguments used by both groups, concluding that the Ḥanafī opinion is to be preferred because it is based on stronger proofs and conforms more closely to the public interest of contemporary Muslims and non-Muslims.